Aid and government fiscal behavior: assessing recent evidence - Morrissey, Oliver (Elsevier, 2014)
This paper reviews evidence published in the last 10 years that has added to our understanding of the effects of aid on government spending and tax effort in recipient countries, with a discussion of when (general) budget support is a fiscally efficient aid modality. Three generalizations are permitted by the evidence: aid finances government spending; the extent to which aid is fungible is over-stated and even where it is fungible this does not appear to make the aid less effective; and there is no systematic effect of aid on tax effort. Beyond these conclusions effects are country-specific.